THE APPLICATION OF LEARNING WITH COGNITIVE CONFLICT APPROACH IN IMPROVING UNDERSTANDING CONCEPT OF PHYSICS OF CLASS VIII STUDENTS OF SMP 40 PEKANBARU - Emiliani Emiliani; Zulirfan Zulirfan; Fakhruddin Z; Februartati Februartati (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
This study aims to determine the improvement of conceptual understanding of physics of class VIII students of SMP Negeri 40 Pekanbaru on the topic of light and optical through learning with cognitive conflict approaches. The type of this research is quasi experiment with population of 172 students of class VIII SMP Negeri 40 Pekanbaru consisted of 4 classes. Two classes were selected to be a research sample based on normality and homogeneity tests on repetition of sound material to obtain experimental and control classes, each of 43 people. The data collected by giving the physics’ conceptual understanding test in Bloom's taxonomy in the form of two tier multiple choice with 14 items. This instrument consists of 7 indicators of conceptual understanding, namely: interpretation, modeling, classifying, summarizing, drawing inference, comparing, and explaining. The result of the research showed that the ability of studens’ concept understanding after the application of learning with cognitive conflict approach was in the good category. The average score of the students’ understanding of the physics concept on the experimental group was higer than the average score of the control group. it can be concluded that learning with cognitive conflict approach can improve conceptual understanding of physics of class VIII SMP Negeri 40 Pekanbaru student on the topic of light and optics.